Public libraries going green - Miller, Kathryn, 1971-; ebrary, Inc. (Chicago : American Library Association, 2010)
Going Green is now a national issue, and patrons expect their library to respond in the same way many corporations have. Libraries are going green with logos on their websites, programs for the public, and a host of other initiatives. This is the first book to focus strictly on the library's role in going green, helping you with collection development, disposal, and recycling issues; green equipment, technology, and facilities; programming ideas with supporting tables and figures; and ways to get the community involved in the process.--From publisher description.
The library's green role -- The library as a green place -- Green services at your library -- The library as green teacher.
Includes bibliographical references (p. 89-95) and index.
Electronic reproduction.
Keywords: Library buildings -- Environmental aspects -- United States; Library buildings -- Energy conservation -- United States; Libraries and community -- United States; Public libraries -- United States; Environmental education -- United States; Electronic books